2022
DOI: 10.1002/cam4.4829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, prognostic factors, and survival trends in esophageal neuroendocrine carcinomas: A population‐based study

Abstract: Background: Esophageal neuroendocrine carcinoma (ENEC) is an extremely rare type of malignancy. Clinical data of ENEC are limited to case reports and case series. More information is needed on its clinical feature, management, and prognosis. Methods: This study collected information of ENEC patients diagnosed pathologically from 2010 to 2018. Data including demographic information, clinical features, and survival trends were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…There are also some additional studies have found that the difference in tumor location does not have a statistically significant impact on patient prognosis ( 24 , 25 ). The findings of this study are consistent with Chen’s research ( 26 ), suggesting that the median survival time of patients with mid-thoracic ESCC is significantly lower than that of the patients with ESCC in the upper and lower segments. This can be attributed to the fact that the middle segment of the esophagus is deeper, surrounded by vital organs and structures, and has comparably less blood supply than the other segments.…”
Section: Discussionsupporting
confidence: 92%
“…There are also some additional studies have found that the difference in tumor location does not have a statistically significant impact on patient prognosis ( 24 , 25 ). The findings of this study are consistent with Chen’s research ( 26 ), suggesting that the median survival time of patients with mid-thoracic ESCC is significantly lower than that of the patients with ESCC in the upper and lower segments. This can be attributed to the fact that the middle segment of the esophagus is deeper, surrounded by vital organs and structures, and has comparably less blood supply than the other segments.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that distant metastasis is a known predictor of outcome further highlights the prognostic potential of MTV and TLG. In addition, lymph node metastasis ( 27 , 28 ), Ki-67 index ( 13 ), surgery ( 26 ), chemotherapy ( 26 ) have also been suggested as significant predictors of survival in esophageal NEC in previous studies. However, the univariate analysis in our study did not reveal significant association between these clinical factors and survival.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study by Chen et al., which included 283 patients with esophageal NEC and over half (53.4%) of the patients presented with distant metastasis at the time of diagnosis, distant metastasis was found to be significantly related to worse survival outcome ( 26 ). This is partly consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms are utilized as a visual numerical graphical tool to forecast the probability of occurrence of a particular event based on data with known factors. In recent years, nomograms have been widely used to predict the prognosis of various cancers, such as esophageal, pancreatic, breast and prostate cancers ( 21 24 ). For gallbladder cancer, several nomograms with different predictive functions have also been developed ( 18 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%